Pension revolution : - Ambachtsheer, Keith P. (Wiley, 2007)
The tectonic plates of governance reform have totally transformed the landscape of governance in publicly traded corporations. Now, Ambachtsheer challenges the owners of those corporations, the institutional investors, to examine themselves and to reform their own fiduciary practices.